A conserved role of IQGAP1 in regulating TOR complex 1 - Tekletsadik, Yemsrach K. (Company of Biologists, 2012)
Defining the mechanisms that control cell growth and division is crucial to understanding cell homeostasis, which impacts human diseases such as cancer and diabetes. IQGAP1, a widely conserved effector and/or regulator of the GTPase CDC42, is a putative oncoprotein that controls cell proliferation; however, its mechanism in tumorigenesis is unknown. The mechanistic target of rapamycin (mTOR) pathway, the center of cell growth control, is commonly activated in human cancers, but has proved to be an ineffective clinical target because of an incomplete understanding of its mechanisms in cell growth inhibition. Using complementary studies in yeast and mammalian cells, we examined a potential role for IQGAP1 in regulating the negative feedback loop (NFL) of mTOR complex 1 (mTORC1) that controls cell growth. Two-hybrid screens identified the yeast TORC1-specific subunit Tco89p as an Iqg1p-binding partner, sharing roles in rapamycin-sensitive growth, axial-bud-site selection and cytokinesis, thus coupling cell growth and division. Mammalian IQGAP1 binds mTORC1 and Akt1 and in response to epidermal growth factor (EGF), cells expressing the mTORC1–Akt1-binding region (IQGAP1(IR-WW)) contained attenuated phosphorylated ERK1/2 (ERK1/2-P) activity and inactive glycogen synthase kinase 3α/β (GSK3α/β), which control apoptosis. Interestingly, these cells displayed a high level of Akt1 S473-P, but an attenuated level of the mTORC1-dependent kinase S6K1 T389-P and induced mTORC1–Akt1- and EGF-dependent transformed phenotypes. Moreover, IQGAP1 appears to influence cell abscission and its activity is elevated in carcinoma cell lines. These findings support the hypothesis that IQGAP1 acts upstream on the mTORC1–S6K1→Akt1 NFL and downstream of it, to couple cell growth and division, and thus like a rheostat, regulates cell homeostasis, dysregulation of which leads to tumorigenesis or other diseases. These results could have implications for the development of the next generation of anticancer therapeutics.